Makerspaces Desa sebagai Sarana Penggalian Potensi Desa untuk Pemberdayaan Masyarakat - Dyah Puspita Srirahayu; Dessy Harisanty; Esti Putri Anugrah; Muhammad Rifky Nurpratama (Jurnal Pengabdian Pada Masyarakat, 2021)
VILLAGE MAKERSPACES AS A MEANS OF EXPLORING VILLAGE POTENTIAL FOR COMMUNITY EMPOWERMENT. The reality around us is that many Indonesians are considered to be still not independent, they still experience difficulties in meeting their daily primary needs, and still need assistance from the Indonesian government. There needs to be a community empowerment program by the local village government, because it is the closest to the community. One of the community empowerments programs that can increase the level of community economic independence is to develop a makerspace in the village. Makerspaces is a space where creative people gather, learn, and create something. This community service is located in Bogo Village, Kapas District, Bojonegoro Regency which has the Moringa Plant icon. This community service partnered with PKK women and KWT women in Bogo Village. The problems that exist in Bogo Village are that there are still only a few variants of processed Moringa that are sold and the product marketing is still lacking. The solution offered is to develop village makerspaces to explore the village's potential deeper, namely the Moringa plant that grows a lot in Bogo Village, then provide training to make Moringa processed variants and digital marketing of the products that have been made.